Prizren as a City-State under Roman-Byzantine Administration - Kryeziu, Kadri (Technium Social Sciences Journal, 2022)
The rule of the Roman Empire left its mark on ancient Dardania as well. At the time of the division of the empire into Roman and Byzantine, Prizren fell under the Byzantine rule. Theranda, as Prizren was called in Roman times, developed as a very important place in many spheres of life, first in trade then in administration and culture. As we know, Rome, at the time of the occupation of the new lands, compulsorily introduced both law and management and administration. The initial cartographic data for Prizren come from the Roman period, when the city with its ancient name, Theranda, is shown on Peutinger's table. Regarding the functioning of Prizren as a city-state or provincial state, according to the Kanun of Prizren of 1570, part of the Sanjak of Prizren were six kazas (districts): Prizren, Hoça, Sesrit (Neubicare), Bihor (important fortification) and Trgovishte (Rozhaje). According to Haxhi Kalfi, in the middle of the XVII century, this sanjak had Perser (Prizren) Suhareka, Havas Prizren (Gora and Opoja), Firqne (Hoqa), Bihor and Trgovishte as kadiluks. The paper treats Prizren since ancient Roman Byzantine times, Prizren as a city-state, Theranda as an important cultural trade centre and as the first administrative centre, a province of the Roman Empire.